Cultural Assimilation of Indonesia-Malaysia in Arena Wati’s Novel Cakra Waruga - Badaruddin, Muhammad Syafri; Sitoto, Simon; Hasyim, Husain (Soegijapranata Catholic University, 2021)
Through the novel with Malaysian background, Arena Wati includes socio-cultural aspects of Bugis-Makassar and Javanese in social interaction of Malaysian community. The aim of the study is to compare cultural assimilation between Indonesia and Malaysia in Arena Wati’s novel, Cakra Waruga. The writing applied multidisciplinary approach which emphasizes the disciplines, such as literature, culture, history and sociology. The analysis of this writing used multidisciplinary approach, which includes intrinsic and extrinsic elements. The study indicates that the occurrence of cultural assimilation between Indonesia and Malaysia was possible due to many Bugis and Makassar people who came and settled in Malaysia. This is due to the existence between the two countries despite their differences but they belong to the same family that is Malay.